Efficacy of VDT PACE‐like regimens in treatment of relapsed/refractory multiple myeloma. Issue 2 (10th November 2017) - Lakshman, Arjun; Singh, Preet Paul; Rajkumar, S. Vincent; Dispenzieri, Angela; Lacy, Martha Q.; Gertz, Morie A.; Buadi, Francis K.; Dingli, David; Hwa, Yi Lisa; Fonder, Amie L.; Hobbs, Miriam; Hayman, Suzanne R.; et al.
Abstract: Experience with intensive chemotherapy for relapsed/refractory multiple myeloma (RRMM) using VDT PACE regimen and its modifications (VDT PACE‐like regimens: VPLRs) outside TOTAL THERAPY trials is limited. We analyzed the outcomes of 141 patients with RRMM who received VPLRs at our center between 2006 and 2017 in an intent‐to‐treat analysis. Median age was 59.7 years and 66.7% of patients were male. A median of 2.2 years (range 0.02‐11.4) separated diagnosis of myeloma and inititation of VPLR. High‐risk cytogenetics were present in 52.4% patients. Patients received a median of 4 (range 1‐14) prior therapies, including stem cell transplant (SCT) in 66.7% patients. Ninety‐five (67.4%) patients received VDT PACE, 20 (14.2%) patients received VD PACE and 26 (18.4%) patients received other VPLRs. Patients received a median of 1 cycle (range 1‐9) of VPLR. We observed ≥ minimal response in 68.4%,  ≥ partial response (PR) in 54.4% and ≥ very good PR in 10.3% patients. Median progression‐free survival was 3.1 months (95% CI, 1.9‐3.9) and median overall survival (OS) was 8.1 months (CI, 6.2‐9.9). One‐hundred and sixteen (82.3%) patients received some therapy after VPLR; 71 (61.2%) received systemic chemotherapy, while 45 (38.8%) underwent SCT. Median OS for those who received SCT after VPLR was 15.1 months (CI, 10.3‐20.8). Age ≥ 60 years (hazard ratio [HR] 2.3 [CI, 1.4‐3.7]; P  = 0.0008) and R‐ISS III stage (HR‐ 2.4 [CI, 1.3‐4.0]; P  = 0.003) predicted shorter OS in patients receiving VPLR. VPLRs are effective in heavily pre‐treated RRMM. In fit patients, SCT can be used to consolidate the response to VPLR.